A method for estimating the position and direction of a leader of a set of moving objects - Francisco Javier Moreno Arboleda; John Freddy Duitama Muñoz; Edison Camilo Ospina (Revista Facultad de Ingeniería Universidad de Antioquia, 2012)
Movement patterns can be identified when studying a group of moving entities such as a group of people, a flock of birds, a school of fish, a convoy of vehicles, among others. In this paper, it is analyzed a pattern, known as leadership. Informally, this pattern is characterized by a moving entity called leader that motivates or represents the behavior of the group in order to reach a goal during a period. A formal method is proposed to estimate the position and the direction where a leader should be located and headed at a time-point in order to lead a group. These estimations can also be useful to check the consistency of the data about a leadership pattern, and to estimate the missing information (position and direction) of a leader at a specific time, i.e., an imputation process. In order to show the expediency of the proposal, a series of experiments were implemented and conducted using Netlogo, a programmable modeling environment for simulating natural and social phenomena.